(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In 1992 and 1993 a Rothamsted type suction trap was used in Valtellina (Sondrio province -1) to collect aphids. The trap worked from April to November. In the first year 61 specimens were catched, belonging to 22 species, during the second year 133 individuals were collected belonging to 15 species. Tue total number of species was 27. Trama (Trama) rara Mordvilko is recorded for the first time for Italy.